1997
DOI: 10.1063/1.1148118
|View full text |Cite
|
Sign up to set email alerts
|

Large area electron beam pumped krypton fluoride laser amplifier

Abstract: Nike is a recently completed multi-kilojoule krypton fluoride (KrF) laser that has been built to study the physics of direct drive inertial confinement fusion. This paper describes in detail both the pulsed power and optical performance of the largest amplifier in the Nike laser, the 60 cm amplifier. This is a double pass, double sided, electron beam-pumped system that amplifies the laser beam from an input of 50 J to an output of up to 5 kJ. It has an optical aperture of 60 cm × 60 cm and a gain length of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…3; i.e., a "top- Using a setup similar to that described in ref. [12], we recorded time-integrated near-field images of several Nike beams on photochromic UV-sensitive PERM film (manufactured by GAF Chemicals). [21] For each beam, we measured the image at both the collimator and the target chamber window during the same laser shot by placing film over one half of the recollimator and allowing the unblocked half of the beam to propagate on to the window.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3; i.e., a "top- Using a setup similar to that described in ref. [12], we recorded time-integrated near-field images of several Nike beams on photochromic UV-sensitive PERM film (manufactured by GAF Chemicals). [21] For each beam, we measured the image at both the collimator and the target chamber window during the same laser shot by placing film over one half of the recollimator and allowing the unblocked half of the beam to propagate on to the window.…”
Section: Resultsmentioning
confidence: 99%
“…This structure, which builds up the beams propagate away from the pupil-plane images at the amplifiers, arises primarily from upstream random phase aberration; it is distinct from the generally long scalelength variations due to residual gain nonuniformities across the amplifier apertures. [12] In angularly-multiplexed KrF systems, it develops primarily in the long delay path optics (e.g., demultiplexing mirrors and focusing lenses) after the final amplifier. The speckle nonuniformities of ISI beams are much smaller than those created by coherent light, and so far they have not caused any serious damage in the Nike output optics because the average fluences (typically less than 0.5 J/cm 2 ) are well below damage threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Nike routinely (up to 20 shots in eight hours) demonstrates efficient laser amplifier extraction (angularly multiplexing), uniform focal spatial profile utilizing induced spatial incoherence (ISI) [4], and pulse shape control. The largest amplifier of the Nike laser system has been discussed in detail elsewhere [5]. Nike is pumped with two counter streaming electron beams.…”
Section: Introductionmentioning
confidence: 99%
“…Such a KrF laser module would be pumped by repetitively pulsed, counterstreaming, large-area electron beams (e-beams). Theory, simulation, [2,3] and experiments [4] performed on the NIKE [5] KrF laser at the Naval Research Laboratory have shown that large-area, e-beam diodes are susceptible to the transittime instability. The instability modulates the electron beam spatially and temporally, producing a wide spread in electron energy and momentum distributions.…”
Section: Introductionmentioning
confidence: 99%